2022
DOI: 10.1111/rda.14106
|View full text |Cite
|
Sign up to set email alerts
|

Immunocastration with gene vaccine (KISS1) induces a cell‐mediated immune response in ram testis: A transcriptome evaluation

Abstract: Immunocastration vaccines achieve their effects through neutralization of the endogenous hormone by the humoral antibody produced against the immunized genes, but there is little information regarding cell‐mediated immune response on the gonadal function of the immunized model is available. In this study, we used ram as a model animal to identify the cellular immune response in testicular tissues of rams immunized with intranasal KISS1 gene vaccine. The immune castration model was evaluated by sexual behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Although the vaccine showed promise for inhibiting male fertility in the ram, the effect was not permanent, as testosterone production and spermatogenesis recovered by weeks 22 to 30 post-immunization ( 537 ). Another study in rams immunized with pKS-asd reported a significant alteration in the expressions of genes associated with cellular immunity specific to the testis ( 469 ). Specific effects were noted on the cytotoxic pathway of Leydig cells mediated by natural killer cells, and it was suggested that these could lead to permanent infertility.…”
Section: Methods Of Sterilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the vaccine showed promise for inhibiting male fertility in the ram, the effect was not permanent, as testosterone production and spermatogenesis recovered by weeks 22 to 30 post-immunization ( 537 ). Another study in rams immunized with pKS-asd reported a significant alteration in the expressions of genes associated with cellular immunity specific to the testis ( 469 ). Specific effects were noted on the cytotoxic pathway of Leydig cells mediated by natural killer cells, and it was suggested that these could lead to permanent infertility.…”
Section: Methods Of Sterilizationmentioning
confidence: 99%
“…In the US, the technology for antibody-mediated immunocontraception received a patent in 2014 ( 467 ). Although most immune methods that only provide contraception and reimmunizations are necessary, studies have shown that sterility can be achieved by using specific methods and immune targets ( 195 , 468 , 469 ).…”
Section: Methods Of Sterilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…vaccines are often safer than other vaccines because they carry only antigen genetic information, are more stable and easier to produce, and can stimulate both humoral and cellular immune responses. 24,38,39 Intrinsic elements of gene vaccine can also activate innate immune responses, thereby enhancing adaptive immune responses against the expressed antigens. Immunization with plasmid DNA antigen provides long-term tissue expression compared with protein antigens, and is potentially able to prime a strong immune response.…”
Section: Inactivated/killed Vaccinesmentioning
confidence: 99%
“…Genetic vaccines contain genetic material such as mRNA or DNA plasmids encoded with one or multiple genes, which are engaged by host defense cells and translated into protein. Genetic vaccines are often safer than other vaccines because they carry only antigen genetic information, are more stable and easier to produce, and can stimulate both humoral and cellular immune responses 24,38,39 . Intrinsic elements of gene vaccine can also activate innate immune responses, thereby enhancing adaptive immune responses against the expressed antigens.…”
Section: Types Of Vaccination During Pregnancymentioning
confidence: 99%